2003
DOI: 10.1111/j.1348-0421.2003.tb03457.x
|View full text |Cite
|
Sign up to set email alerts
|

Genotype and Subtype Analyses of Hepatitis B Virus (HBV) and Possible Co‐Infection of HBV and Hepatitis C Virus (HCV) or Hepatitis D Virus (HDV) in Blood Donors, Patients with Chronic Liver Disease and Patients on Hemodialysis in Surabaya, Indonesia

Abstract: Hepatitis B virus (HBV) infection is a worldwide health problem. The prevalence of HBV carriers varies from 0.1 to 2% in low prevalent areas to 10 to 20% in high prevalent areas. Indonesia is among the HBV high prevalent countries (16). The identification of the common determinant a and two pairs of allelic variations, d/y and w/r, has lead to the definition of the four major subtypes of hepatitis B surface antigen (HBsAg), adw, adr, ayw, and ayr (3,13,18,37). Another classification system, which is based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 37 publications
4
29
0
4
Order By: Relevance
“…However, several data resources exist regarding the prevalence of HBV and HIV among the general population in several parts of Indonesia (6,9,13,15,25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several data resources exist regarding the prevalence of HBV and HIV among the general population in several parts of Indonesia (6,9,13,15,25).…”
Section: Discussionmentioning
confidence: 99%
“…Indonesia is a multiethnic country. We previously reported the distribution of the genotypes and subtypes of HBV across several geographical areas in Indonesia (9,13). In addition, we reported the prevalence of each HCV subtype, including HCV subtype 1c (HCV-1c), among various clinical populations in Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the findings of the above studies in Vietnamese, a study by Song et al reported that genotype A was very commonly observed in HBV-infected Vietnamese patients (98.7%), that the pre-core mutation (G1896A) was not found, and dual core promoter mutations (A1762T/G1764A) were very rare in HCC patients (8%) and were not found in LC patients, CH patients or asymptomatic carriers (ASC) (33). The results reported by Song et al were very surprising, since the results of many other studies in East Asia and some in Vietnam, with only the exception of studies in the Philippines, showed that genotypes B and C were the major HBV genotypes in this region and mutations in the core promoter and pre-core regions were frequently found (8)(9)(10)(12)(13)(14)(15)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(34)(35)(36)(37)(38).…”
Section: Introductionmentioning
confidence: 95%
“…16 dilaporkan bahwa genotipe B sebagai satu-satunya genotipe pada penderita hepatitis B kronik dan penderita hemodialisis di Surabaya. Perbedaan hasil ini mungkin disebabkan adanya perbedaan asal subjek penelitian, subjek penelitian kali 16 berasal dari daerah yang didominasi genotipe B. Hal ini didukung oleh hasil penelitian yang dilaporkan dari kota Padang sebagai daerah yang memiliki kedekatan geografik dan etnik dengan kota Pekanbaru, bahwa genotipe C merupakan 65% genotipe VHB yang ditemukan pada penderita hepatitis B kronik. 15 Selain itu, pada penelitian tersebut juga diketahui bahwa subtipe adr adalah subtipe HBsAg yang paling banyak ditemukan, yaitu sebesar 67,6%, lebih kurang hampir sama dengan yang ditemukan pada penelitian ini, yaitu 60%.…”
Section: Pembahasanunclassified